2020
DOI: 10.32598/ppj.24.4.40
|View full text |Cite
|
Sign up to set email alerts
|

Proton pump inhibitors in Iranian population: from clinical regimens to pharmacogenomics

Abstract: Proton pump inhibitors (PPIs) are one of the highly prescribed or over-the-counter available medications among Iranians, mainly to treat conditions such as helicobacter pylori infection, gastroesophageal reflux disease or frequent heartburn. In recent years, several reports have shown potential adverse effects of PPI administration among which cardiovascular adverse events, myocardial infarction and chronic kidney disease are considered as the greatest risks. Recent addition of proton pump inhibitors to the li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 103 publications
0
2
0
Order By: Relevance
“…Studies have shown increased activity of CYP2C19 and therefore, rapid metabolization of PPIs in Americans and central Europe, whereas East Asian population, including Japanese and Chinese, are slow metabolizers 22–26 . Iranian are also considered as rapid metabolizers 27 . However, in our study, we used esomeprazol, a second‐generation of PPIs which is less influenced by CYP2C19 activity 28…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Studies have shown increased activity of CYP2C19 and therefore, rapid metabolization of PPIs in Americans and central Europe, whereas East Asian population, including Japanese and Chinese, are slow metabolizers 22–26 . Iranian are also considered as rapid metabolizers 27 . However, in our study, we used esomeprazol, a second‐generation of PPIs which is less influenced by CYP2C19 activity 28…”
Section: Discussionmentioning
confidence: 96%
“…[22][23][24][25][26] Iranian are also considered as rapid metabolizers. 27 However, in our study, we used esomeprazol, a second-generation of PPIs which is less influenced by CYP2C19 activity. 28 Amoxicillin, a beta-lactam antibiotic, is currently extensively employed to treat H. pylori.…”
Section: Discussionmentioning
confidence: 99%